PROFILE OF NEUROLOGICAL MANIFESTATIONS IN PRIMARY SJOGREN’S SYNDROME - M S Panchovska; J I Slieilanov; R M Sloilov (Научно-практическая ревматология, 2002)
Objective. To establish the frequency and the type of the neurologic manifestations in pts with primary Sjogren’s syndrome in Bulgarian population. Material and methods. For the period of five years 65 pts with primary Sjogren’s syndrome fulfilling the European clasification criteria for diagnosis were observed. There were evaluated the neurological and the internal status. Electromyography, computer tomography, audiometric investigations were realised. Results. In 28 patients (43,06%) neurological manifestations and diversious in the diagnostic tests were found. Some of the manifestations showed a relapsing character (neuropathy of the n. trigemini), some of them showed a partial disability (mononeuritis multiplex). Conclusion. The engagement of the nervous system occurs in a great number of patients with primary Sjogren’s syndrome. The prognosis of the neurologic manifestations depends on Lhe accurate diagnosis and treatment.